2016
DOI: 10.1007/s10549-016-3943-4
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer-specific mortality in small-sized tumor with node-positive breast cancer: a nation-wide study in Korean breast cancer society

Abstract: Tumor size and number of lymph node (LN) metastases are well known as the most important prognostic factors of breast cancer. We hypothesized that very small breast cancers with LN metastasis represent a progressive biologic behavior and evaluated tumor size stratified by LN metastasis. Data between 1990 and 2010 were obtained retrospectively from the Korean Breast Cancer Society Registry with inclusion criteria of female, non-metastatic, unilateral, and T1/2 breast cancer. We collected the following variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Our study found age to be an independent risk predictor of OS in patients with small tumors without LNM. These results are in line with those of previous studies (5,18,19).…”
Section: Discussionsupporting
confidence: 94%
“…Our study found age to be an independent risk predictor of OS in patients with small tumors without LNM. These results are in line with those of previous studies (5,18,19).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, statistically significant differences were found between the low-proliferation group and the highproliferation group with regard to tumor size, histological grade, and axillary node metastasis, which might be associated with the cell proliferation and cancer progression in the high-proliferation group (15,36). Ryu et al (37) supposed that many clinicians might underestimate the risks in patients with smaller breast tumors, but the possibility of biologically aggressive characteristics might actually be increased for patients with small tumors with lymph node metastases. Considering this, more attention should be given to a T1 IDCs with a high Ki-67 index in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, there has been a steady increase in the incidence of T1N0 breast cancer due to accessible breast cancer screening programs in Korea [ 5 , 6 ]. Among patients with T1N0 breast cancers, the prevalence of patients with T1c stage is higher than that of patients with T1a or T1b stage [ 7 ]. Therefore, it is of clinical importance to determine the optimal treatment guidelines for patient with T1c stage TNBC breast malignancies.…”
Section: Introductionmentioning
confidence: 99%